Screening-detected rheumatic heart disease can progress to severe disease. Issue 2 (28th November 2016) - Engelman, Daniel; Wheaton, Gavin R; Mataika, Reapi L; Kado, Joseph H; Colquhoun, Samantha M; Remenyi, Bo; Steer, Andrew C
Abstract : Objectives: Echocardiography is a sensitive test for rheumatic heart disease (RHD) screening; however the natural history of RHD detected on screening has not been established. We aimed to evaluate the progression of screening-detected RHD in Fiji. Methods: All young people previously diagnosed with RHD through screening, with echocardiograms available for review, were eligible. All baseline echocardiograms were reported again. Participants underwent follow-up echocardiography. A paediatric cardiologist determined the diagnosis using the World Heart Federation criteria and assessed the severity of regurgitation and stenosis. Results: Ninety-eight participants were recruited (mean age, 17 years; median duration of follow-up, 7.5 years). Two other children had died from severe RHD. Fourteen of 20 (70%) definite RHD cases persisted or progressed, including four (20%) requiring valve surgery. Four (20%) definite RHD cases improved to borderline RHD and two (10%) to normal. Four of 17 (24%) borderline cases progressed to definite RHD (moderate: 2; severe: 2) and two (12%) improved to normal. Four of the 55 cases reclassified as normal at baseline progressed to borderline RHD. Cases with a follow-up interval >5 years were more likely to improve (37% vs 6%, p=0.03). Conclusions: The natural history of screening-detected RHD is not benign. Most definite RHD cases persist and others may require surgery or succumb. Progression of borderline cases to severe RHD demonstrates the need for monitoring and individualised consideration of prophylaxis. Robust health system structures are needed for follow-up and delivery of secondary prophylaxis if RHD screening is to be scaled up.